COMPARATIVE STUDY OF FP - GROWTH AND APRIORI IN GROCERY ANALYSIS - Adi, Ahmad Cahyono (Universitas Royal, 2024)
Abstract: The growing business environment causes the business world to create in order to continue to survive, one of which is by increasing sales. One way is to use the data approach. One method of data approach that is widely used is Market Basket Analysis. This study uses the Market Basket Analysis method with the a priori algorithm and FP-Growth. Grocery dataset analysis using two algorithms, Apriori and FP-Growth using a minimum support parameter of 0.45, has results sorted by the top 10 associations with the best confidence value. The association with the highest support value found is